Solid state doping of CdxHg₁₋xTe epitaxial layers with elements of V group - Vlasov, A.P.; Bonchyk, A.Yu.; Fodchuk, I.M.; Barcz, A.; Swiatek, Z.T.; Zaplitnyy, R.A. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2006)
Presented here are the results of studying the controlled doping with elements of V group of the periodic table, arsenic As and antimony Sb, of narrow gap CdxHg₁₋xTe epitaxial layers during the isothermal growth from the vapour phase by the evaporation-condensation-diffusion method. Three types of impurity sources have been used for solid state doping: homogeneously doped with As(Sb) single crystal substrates of CdTe, As doped buffer CdyHg₁₋yTe (y > x) epitaxial layers obtained by RF sputtering in mercury glow discharge onto undoped CdTe substrates, and As(Sb) implanted undoped CdTe substrates. The results of comparative analysis of galvano-magnetic measurements and SIMS spectra indicated very high, practically nearly ~100 %, electrical activity of dopants in the CdxHg₁₋xTe epitaxially grown layers.